Allometric Scale Corrects Performance Outcomes in Special Judo Fitness Test - Franco-Alvarenga, Paulo Estevão; Ferreira, Guilherme Assunção; Lima-Silva, Adriano Eduardo; Bertuzzi, Rômulo; Pires, Flávio Oliveira; De Oliveira, Fernando Roberto (International Journal of Sports Medicine, 2019)
We compared results of Special Judo Fitness Test (SJFT) performance of young athletes of two different age categories after correcting body mass (BM) variations by allometric scales. Thirty young judokas (14.2±3.6 years) belonging to two age categories underwent an SJFT: under 15 (U15) years old (12.1±2.4 years; 46.5±15.6 kg; 152.4±11.2 cm) and under 21 years old (U21) (18.2±0.8 years; 77.1±23.5 kg; 174.2±8.9 cm). Allometric exponents of −0.33 and 0.67 were used to correct the influence of BM variations on SJFT performance results. After correction using the –0.33 exponent, U21 showed a higher number of throws (TNT) than U15 (85.5±9.9 and 68.8±12.0, p<0.05, respectively), although the SJFT index had been similar between these groups (67.3±10.1 and 61.7±8.1, p>0.05, respectively). In contrast, TNT normalized by the 0.67 exponent was higher in U15 than U21 (1.55±0.29 and 1.17 ± 0.25, p<0.05, respectively). Likewise, the SJFT index was higher in U15 than in U21 when using the same exponent (1.55±0.29 and 1.17±0.25, p<0.05, respectively). In conclusion, the −0.33 exponent may be useful to remove the influence of BM variations, thus discriminating SJFT performance results in U15 and U21 judokas. Moreover, the 0.67 exponent may overestimate SJFT indices in low-age judokas.
Keywords: body mass; young athletes; performance correction; judokas